On the formation of a waterproofing shell around the underground structure lining in watered ground - Uglyanitsa Andrey (EDP Sciences, 2021)
To prevent the filtration of groundwater into the used underground structure in operation through its lining, it is proposed to make two waterproofing shells by the underground method around the outer surface of the lining of an underground structure; the upper one is made of the soil mass compacted by cementation with reduced water permeability and the lower one is made of the silicate cement. To make the upper shell, boreholes are drilled from an underground structure through its lining and the cement mortar is alternately injected through them into the watered ground providing its hydraulic fracturing; and to make the lower shell, injection pipes with a diameter of 102-152 mm are installed between the boreholes in the lining flush with its outer surface, the silicate cement mortar is alternately injected into the injection pipes, an incipient crack is created between the outer surface of the lining and the ground under the action of the mortar injection pressure on the ground opposite the injection pipe, an incipient crack is hydraulically extended along the contact of the lining with the ground and filled with the silicate cement mortar until refusal to absorb it. To determine the optimal parameters of the hydraulic separation process, tests were carried out on the laboratory table simulator.